Risk-averse optimal bidding strategy considering bi-level approach for a renewable energy portfolio manager including EV parking lots for imbalance mitigation - Cicek, Alper; Erdinc, Ozan (ELSEVIER, 2021)
In this study, a bi-level optimum bidding strategy is proposed in which a renewable energy portfolio manager (REPM), including electric vehicle parking lots (EVPLs) for imbalance mitigation, participates in the day-ahead (DA) market and balancing market (BM). In the upper-level problem, the total gain of REPM is maximized, while in the lower-level problem, the loss of each portfolio participant is minimized according to the specified reference value. The line capacities for bi-directional transactions with the grid are taken into consideration during the decision-making process of REPM. In the study, uncertainties for the DA market and BM price data, renewable energy productions, and electric vehicle (EV) behaviors are addressed by stochastic approach. The risk management is handled with the conditional value-at-risk (CVaR) method for loss or loss from profit that may occur due to uncertainties. Moreover, various case studies are carried out with Finland and Turkey electricity market data to prove the effectiveness of the proposed model. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Bi-level optimization; Electric vehicle parking lot; Electricity market; Optimal bidding; Renewable energy portfolio manager; GENERATION; Energy & Fuels; Engineering